Proliferation and biochemical analyses of osteoblast/osteoclast differentiation from human mononucleated cells - Siti Afeefah Mohamad Yusof,; Rohaya Megat Abdul Wahab,; Sahidan Senafi,,; Zaidah Zainal Ariffin,; Mohamad Abdul Razak,; Shahrul Hisham Zainal Ariffin, (Universiti Kebangsaan Malaysia, 2011)
Stem cell is defined as the ability of the cell to proliferate themselves and differentiate into more than one type of cells. Human mononucleated cell (MN cell) is a suspension cell that was isolated from peripheral blood that was originated from monocyte-machrophage lineage or hematopoietic stem cells. The cells were cultured for 30 days in complete media (CM) which consist of Alpha Minimal Essential Medium (αMEM) with 2% (v/v) Penicillin-Streptomycin and 10% (v/v) Newborn Calf Serum (NBCS). The respective cells were differentiated at day 7 after in vitro proliferation in CM into osteoblastic cells by adding ascorbic acid and β-glycerophosphate. In addition, human recombinant Receptor Activator of Nuclear Factor-β Ligand (hrRANKL) and human recombinant Macrophage-Colony Stimulating Factor (hrM-CSF) were added to induce osteoclastic differentiation of MN cells. Cells that were cultured in CM served as a control and were subjected to the same approach as differentiated cells. The 30 days cultured cells in CM showed a significant increment (p < 0.05) of viable cells compared to day 0 (n=3). The specific activity of Alkaline Phosphatase (ALP) for osteoblast differentiation and Tartrate Resistant Acid Phosphatase (TRAP) for osteoclast differentiation were evaluated via biochemical assay until day 14 and day 10 for osteoblast and osteoclast sample, respectively. ALP and TRAP enzyme showed a significant increment (p < 0.05) after 14 and 10 days of differentiation compared to control cells. As a conclusion, human mononucleated cells are believed to have the potential to be defined as a multipotent stem cell based on their fulfillment of stem cell characteristics